Cleanliness of transferred graphene by acetone and acid - Liu, Zheng; Liu, Yuxin; Zheng, Wenbin; Ding, Yang; Liu, Wenjun; Wen, Yu; Guo, Hongxuan; Hou, Jixin (Frontiers in Materials, 2023)
The cleanliness of transferred graphene is crucial for its application in various fields. The presence of residues of polymethyl methacrylate (PMMA) on the surface of transferred graphene has a negative impact on its transparency, transport, and other critical properties. In this study, we propose an alternative method to reduce such residues by using acetic acid instead of the commonly used acetone. The effects of treating graphene with acetic acid and acetone are comprehensively evaluated through optical microscopy, scanning electron microscopy, Raman spectroscopy, and X-ray photoelectron spectroscopy. The results of this study demonstrate a significant reduction in surface residue when graphene is treated with acetic acid, compared to acetone treatment. Additionally, we applied this method to fabricate graphene-based supercapacitors and compared the results using acetic acid and acetone. This reduction in residue holds great promise for advancing the development of high-quality graphene devices.